أثر احتياطيات إنتاجية العمل على أنظمة الإنتاج - جنود، غدير سمير (جامعة البعث, 2020)
تعد وظيفة الإنتاج الوظيفة الأكثر أهمية في المنظمات الإنتاجية والخدمية، لأنها تؤدي إلى خلق السلع والخدمات من خلال تحويل مدخلات نظام التشغيل إلى مخرجات. ويمكن الحكم على أداء نظام الإنتاج من خلال الإنتاجية، فالإنتاجية - كعلاقة بين المخرجات والمدخلات - هي مقياس لكفاءة إدارة الإنتاج، فوجود إنتاجية عالية في منظمة ما يعني: أن هناك إدارة إنتاج ناجحة والعكس صحيح. والإنتاجية يمكن التأثير عليها وتطويرها والتحكم بها من خلال مجموعة عناصر وظروف داخلية وخارجية، لكن الأهم من ذلك هو التأثير على جملة عناصر. البيئة الداخلية للمنظمة واستغلالها بشكل أمثل للوصول إلى إنتاجية عالية. تعالج الدراسة هذه مفهوم احتياطيات نمو إنتاجية العمل كجملة قوى كامنة يمكن استغلالها واستثمارها بشكل أمثل، بحيث يؤدي ذلك إلى توفير في نفقات العمليات والوظائف. توصلت الدراسة إلى أن اكتشاف تلك الاحتياطيات واستخدامها يؤدي إلى: تقليل كثافة العمل للإنتاج، والاستغلال الأفضل لوقت العمل، وتغيير في التركيب الهيكلي لفئات العمال، ودفع المشاريع لتعميق التخصص وحسن التوزيع الأمثل للورديات.
A production function is the most important function in manufacturing and service organizations, because it leads to the creation of goods and services through transforming the inputs of the operating system into outputs. The performance of the production system can be evaluated by the productivity, the productivity - As a relationship between the outputs and the inputs - is a measure of the production management efficiency, and the high productivity in an organisation means: The attached study addresses the concept of "Reserves of Labour Productivity Growth" as a set of potential powers that can be invested optimally, in which can save the expenses of the operations and functions. Also, it means using precise scientific principles in the management, and using the cognitive output to achieve the best results at the lowest costs. In addition, this study addresses the utilisation conditions of the Labour Productivity Growth Reserves, with analytical review supported by examples and practical case studies, and in a way that can reduce costs and waste of resources. The study concluded that discovering these reserves and using them lead to: Reducing labour intensity of production, better use of work time, specialisation and improve the optimum distribution of shifts.
Keywords: الإنتاجية -- إنتاجية العمل -- أنظمة الإنتاج